Analysis of influencing factors of visual working memory in young adult patients with schizophrenia. Issue 3 (14th December 2018) - Zhang, Li; Ran, Xuemei; Li, Ting; Ku, Yixuan; Liu, Li; Huang, Tingming; Yan, Wenjia
Abstract : Background: Patients with schizophrenia have general cognitive impairments, and the impairment of working memory is considered to be the basis of cognitive impairments. The research on visual working memory, one of the subcomponents, is getting more and more attention. However, the influencing factors which cause the deficits of visual working memory in patients with schizophrenia have not been clearly explained. To provide evidence for cognitive impairment interventions, the present study explored the factors influencing the deficits of patients' visual working memory. Aim: The present study discussed the relevant factors influencing the visual working memory of patients with schizophrenia by measuring the accuracy of the visual working memory of patients with schizophrenia and healthy controls. Methods: Colour-recall paradigm was employed to measure the accuracy of the visual working memory of 61 healthy controls and 61 patients who met the International Classification of Diseases, Tenth Revision diagnostic criteria for schizophrenia. The age range of subjects was 18–50. Scale for the Assessment of Positive Symptoms (SAPS) and Scale for the Assessment of Negative Symptoms (SANS) were used to evaluate the patients' clinical symptoms. Results: Compared with the healthy control group, the accuracy of visual working memory of patients with schizophrenia was significantly impaired ( t =3.062, p =0.003). The accuracy of visual working memory of patients with schizophrenia was not related to age ( r =0.023, p =0.860), the age of onset ( r =−0.003, p =0.979), the duration of illness ( r =−0.038, p =0.769), education level ( r =−0.181, p =0.162), continuous working time before illness ( r =−0.107, p =0.413) or the daily dose of antipsychotic drugs ( r =0.062, p =0.635); however, it was positively related to the number of hospitalisations ( r =0.471, p <0.001). The total score of Scale for the Assessment of Positive Symptoms (SAPS) was negatively related to the accuracy of visual working memory ( r =−0.388, p =0.005), while the total score of Scale for the Assessment of Negative Symptoms (SANS) ( r =0.416, p =0.001), the total score of diminished emotional expressiveness ( r =0.352, p =0.005) and the total score of attention disorder ( r =0.310, p =0.015) were positively related to the accuracy of visual working memory. Patients using a single drug and those using multiple drugs were compared with each other. They were not significantly different in age ( t =0.010, p =0.992), the number of hospitalisations ( t =0.656, p =0.514), the duration of illness ( t =0.701, p =0.486), the total score of SANS ( t =0.078, p =0.938), the total score of SAPS ( t =1.815, p =0.079) and the daily dose of antipsychotic drugs ( t =1.794, p =0.078). However, in order to explore whether single or combined drug use would affect the accuracy of visual working memory of patients with schizophrenia, the present study also compared these two groups' different S0 values of the accuracy of visual working memory. The results showed that the accuracy of visual working memory of patients with schizophrenia with combined drug use was significantly better than that of patients with single drug use ( t =2.515, p =0.015, independent sample t-test). Conclusion: The present study indicates that the visual working memory of young adult patients with schizophrenia is impaired compared with the healthy people within the same age range. The impairment is more obvious in patients who have multiple hospitalisations and suffer from severe negative symptoms. The impairment in patients with more severe positive symptoms is not very obvious. Combined drug use is likely to alleviate the impairment.